Digital sobriety: From awareness of the negative impacts of IT usages to degrowth technology at work - Péréa, Céline; Gérard, Jessica; de Benedittis, Julien (Technological forecasting & social change, 2023)
The rise of digital technologies has led to growing concern over their environmental impact, prompting the emergence of the phenomenon of digital sobriety. Rooted in the principles of degrowth technology, digital sobriety advocates for reduced technology usage to create a more sustainable society. However, it contrasts with typical frameworks that promote the continued use of IT. Furthermore, it runs counter to the prevailing trend of digital transformation within organisations, which is expected to expand in the future. As a result, it challenges conventional approaches to IT usage and the associated contextual factors. The purpose of this paper is to investigate the concept of digital sobriety, examining its relationship to conventional approaches as well as the degrowth technology perspective. The study explores how digital sobriety is implemented within organisations and how it is perceived by IT users. Thirty-three participants from IT companies were included and the scope and characteristics of the phenomenon of digital sobriety were identified, including five levels of IT user maturity: refutation, inaction, substitution, optimisation, and disadoption/degrowth. The results highlight the need to balance the internal and external factors of digital sobriety and identify different trajectories of digital sobriety as socio-technical imaginaries for the future of IT. •Digital sobriety is a techno-scepticism perspective of Green IT•Digital sobriety implies a socio-technical transition to technological degrowth•A paradoxical transition occurs when organisations combine digital transformation strategies with digital sobriety•Discrepancies can occur between voluntary digital sobriety transitions and IT users’ needs for coercive transition•Different levels of digital sobriety are displayed ranging from opposition to sober IT practices to IT disadoption/degrowth